Effects of italicized angle and turning angle on shale gas nanoflows in non-straight nanopores: A nonequilibrium molecular dynamics study. (15th October 2020) - Zhang, Mingmin; Guo, Guang-Jun; Tian, Huiquan; Zhang, Zhengcai; Gao, Kai
Graphical abstract: Highlights: Nanopore's roughness affects methane flow to a greater extent than nanopore's shape. The italicized angle promotes methane flow in both smooth and rough nanopores. The turning angle impedes the flow in smooth nanopore but promotes it in the rough. The energy barrier at knee point decisively controls the flow in bending nanopores. Abstract: Non-equilibrium molecular dynamic simulations were performed to investigate the effects of the italicized angle and turning angle of non-straight nanopores on the flux of shale gas, with considering smooth and rough porous surfaces respectively. First, the flux data in smooth nanopores are always larger than that in the rough because the rough surface results in the stronger adsorption and slower flow-velocity profiles than the smooth. Second, the italicized angle promotes the methane flow for both smooth and rough nanopores. It is explained that the energy barrier located at the entrances of nanopores reduces with increasing the italicized angle. Moreover, the average Lennard-Jones (LJ) potential of nanopores, a resistance for particles across these nanopores, also weakens with the angle. Third, however, the turning angle shows different effects depending on the roughness. It impedes the methane flow in smooth nanopores but promotes the flow in rough nanopores. The decisive factor lies in the energy barrier locating at the bending point, which plays a prominent impeding impact in smooth nanopores but unapparent in rough nanopores, while the average LJ potential commonly promotes the flow for both surfaces with increasing the turning angle. To the best of our knowledge, this is the first reported study clearly distinguishing the effects of italicized angle and turning angle on nanoflow. These observations are very useful for understanding the transport of shale gas in tortuous porous networks in shale as well as the flow in carbon nanotubes.